Nepheline crystallization and the residual glass composition: Understanding waste glass durability. (6th April 2020) - McClane, Devon L.; Amoroso, Jake W.; Fox, Kevin M.; Hsieh, Madison C.; Kesterson, Matthew R.; Kruger, Albert A.
Abstract: The vast majority of High‐Level Waste (HLW) originating from defense nuclear programs is sequestered and immobilized in borosilicate glass. Borosilicate glass is universally accepted for immobilizing HLW, but its efficiency has limitations based on the compositional makeup of the waste stream. The chemical durability of the glass is the most important factor in determining the longevity and usefulness of the final glass waste form. The primary detriment to this durability in glasses containing high levels of aluminum is nepheline (NaAlSiO4 ) crystallization, as it is generally accompanied by a measurable decrease in the glass's chemical durability. This work seeks to understand nepheline crystallization, within the context of thermal history, and to elucidate the influence of compositional shifts in the residual glass (after crystallization) on the measured durability. The results presented within show a distinct deviation in leaching behavior as a function of structural makeup (calculated Q units). This understanding will provide practical information required for broadening glass compositional regions needed to more efficiently vitrify HLW.